P008 Long term neurophysiological effects of the gluten-free diet in adult celiac patients: A TMS study. Issue 3 (March 2017) - Cantone, M.; Ricceri, R.; Pennisi, M.; Ferri, R.; Pennisi, G.; Bella, R.; Lanza, G.
Abstract : Introduction: Celiac disease (CD) may initially present as a neurological disorder or be associated with neurological complications. In a previous study with Transcranial Magnetic Stimulation (TMS) in de novo CD patients, an imbalance between excitatory and inhibitory synaptic excitability was observed, suggesting a subclinical involvement of GABAergic and glutamatergic neurotransmission in asymptomatic subjects [Pennisi, et al. PLoS One 2014;9(7):e102790]. After a median period of 16 months of gluten-free diet (GFD), a global increase of cortical excitability was reported, hypothesizing a glutamate-mediated compensation for disease progression [Bella et al. PLoS One 2015;10(6):e0129218]. Objectives: To evaluate the long term changes of cortical excitability to TMS after a longer GFD. Materials and method: Ten patients (median age: 36 years; 6 F) on adequate gluten restriction for a median period of 4.3 years were enrolled and age-matched with 10 healthy controls (median age: 37.5 years; 7 F). Clinical, cognitive and neuropsychiatric features were assessed, as well as cortical excitability by means of single- and paired-pulse TMS from the first dorsal interosseous muscle of the dominant hand. TMS measures consisted of: resting motor threshold; motor evoked potentials; central motor conduction time; cortical silent period; intracortical inhibition and intracortical facilitation (ICF). Results: Patients showed a statistically significant enhancement of ICF at interstimulus interval of 10 ms (1.40 ± 0.41 vs 0.78 ± 0.36, p < 0.01) and 15 ms (1.49 ± 0.39 vs 1.02 ± 0.69, p < 0.05) compared to controls. The other TMS parameters, as well as clinical data were similar to those of controls. Neurological examination and CD-related antibodies were normal. Conclusion: Long-lasting adherence to the GFD may modulate the TMS profile towards a pattern globally similar to that of normal subjects. In this new investigation, the length of the dietary regimen was able to induce a recover to a great extent of the gluten-associated electrocortical dysfunction. The persistence of hyperfacilitation may indicate a glutamate-mediated functional reorganization, probably triggered by the immune system dysregulation in CD and related to phenomena of long-term plasticity.